18F-fluorodeoxyglucose uptake in advanced gastric cancer correlates with histopathological subtypes and volume of tumor stroma. Issue 145 (December 2021) - Seko-Nitta, Ayumi; Nagatani, Yukihiro; Murakami, Yoko; Watanabe, Yoshiyuki; Nitta, Norihisa; Murata, Kiyoshi; Takemura, Shizuki; Murata, Satoshi
Highlights: Some gastric cancers show poor FDG uptake and may be barely recognizable by PET. The tumor stroma was confirmed by CD34 staining and compared with FDG uptake. CD34 is known to be expressed in the tumor stroma. FDG uptake was significantly lower in gastric cancer with strong CD34 expression. Tumor stroma is an attractive target in cancer diagnosis and treatment. Abstract: Purpose: The aim of this study was to investigate the correlation between preoperative 18 F-fluorodeoxyglucose (FDG) uptake and histological subtypes, amount of tumor stroma in advanced gastric cancer (GC), and clinical outcomes. Methods: We evaluated 56 patients (male/female, 42:14; mean age, 69 years) with advanced GC who underwent surgical resection at our institution and positron emission tomography–computed tomography with 18F-FDG prior to surgery. We used the maximum standardized uptake value (SUVmax) of the tumor and the tumor-to-liver ratio (TLR) of the SUVmax for the analysis. The SUVmax and TLR correlated with histological subtypes, immunohistochemistry (IHC) for CD34, and recurrence-free survival (RFS). Tumor stroma in GC was evaluated by CD34 expression. GCs were classified according to the Lauren and World Health Organization (WHO) classifications. Results: The average FDG uptakes (SUVmax) were 4.17% and 14.04% in diffuse and intestinal type GCs, respectively, according to the Lauren classification, and 4.17%, 13.87%, 7.70%, 9.71%, and 19.45% in the poorly cohesive, tubular, mucinous, and papillary adenocarcinomas, respectively, according to the WHO classification. The FDG uptake in diffuse type was significantly lower than that in the intestinal type (p = 0.000). The SUVmax and TLR of the CD34(+) group (mean SUVmax, 5.50; TLR, 1.56) were significantly lower than those of the CD34(−) group (mean SUVmax, 14.09; TLR, 4.09). RFS was not associated with TLR or CD34 expression. Conclusion: GC, which has abundant tumor stroma characterized by high CD34 expression on IHC, shows low FDG uptake.